(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2022)
In the article, thoughts on the issues of communication and interaction between people are put forward. In particular, the psychological conflict, situational, meaningful and motivational obstacles that arise in the process of communication and their characteristic aspects are shown. Also, the role and characteristic features of barriers in communication in the system of human relations are mentioned.